Vitamin D3 supplementation in HIV infection: effectiveness and associations with antiretroviral therapy - Coelho, Lara (2015)
Fundação Oswaldo Cruz. Instituto Nacional de Infectologia Evandro Chagas. Laboratório de Pesquisa Clínica em DST/AIDS. Rio de Janeiro, RJ, Brasil.